An investigation into the sensory mechanisms underlying the two point threshold, with particular reference to the practice effect - Gradwell, Peter Bertram (Rhodes University, Faculty of Humanities, Department of Psychology, 1971)
The two point threshold was studied extensively by the psychophysical experimenters of the last century. More recent formulations in signal detection theory have suggested that the statements of these workers about absolute thresholds should be viewed with caution. This study investigates the two point threshold in the light of these formulations, and has two main aims :- (1) To state and deal with the problem of relating a limitation in perceptual ability, such as that which is represented by the two point threshold, to the receptor organisation of the body. (2) To demonstrate a practice effect on the two point threshold, and to consider this in the light of (1) above. To fulfil these two aims, a model of the neural mechanisms underlying the discrimination of two points applied to the skin is proposed, and this is able to accommodate what is known of the two point threshold. Although the model is simple it explicitly accounts for size transfer and the practice effect, and provides some clues as to the type of neural mechanism capable of producing them. The practice effect is demonstrated experimentally, and the results are then referred to the model proposed. The physiology of an organism sets the limits for its behaviour. 'The first aim is thus an important one, in that it considers a specific case of this general problem. And secondly, the practice effect on the two point threshold is typical of a number of fairly simple "learning" phenomena, which are part of the psychologists' study of learning.
Keywords: Sensorimotor integration; Perceptual-motor learning